Multi-metabolic altered patterns and cardiovascular risk factors associated to hypertension in the community. - Alexis Ocampo Segura.; Yoel Alberto Hernández Rodríguez.; Benigno Figueiras Ramos.; Raúl López Fernández; Mikhail Benet Rodríguez (Medisur)
Fundaments: Among other factors, hypertension , hypercholesterolemia and hyperinsulonemia form the so called metabolic syndrome Many studies relate hypertension to other risk factors and to metabolic-endocrine disorders. Objective: To know the relationship between Hypertension and hypercholesterolemia and other cardiovascular risk factors in a community of Cienfuegos city, Cuba. Method: Study of non paired cases and controls . the cases gathered 60 hypertensive patients aged 18 or more years without discrimination of sex, skin color, and other socio demographic features of the population and the control group gathered 60 non- hypertensive individuals from the same population. Results: Family history of hypertension OR:64( 29:14,19) and alcohol consumption OR: 19,8 ( 4,6:84,8) were the most frequent risk factors in the population. The presence of Diabetes mellitus OR 7,8( 2,7:22,4) and dyslipidemia OR 2,7 ( 1,3: 5,6) were the endocrine-metablic factors that associated the most to hypertension Important was the relationship between altered tolerance to glucose and risk factors OR: 14,49 ( 3,64: 57,67) and the relationship altered tolerance to glucose and familial antecedents of hypertension in hypertensive patients which showed a significant association. Conclusion: In the community under study family history of hypertension, alcohol consumption, diabetes mellitus, dyslipidemia and altered glucose are strongly associated to hypertension and constitute risk factors that should be taken into consideration in order to diminish the mortality rate due to vascular disorders.